The deterministic Teaching of probability: La Enseñanza determinista de la probabilidad - B., Geovanni Sanabria (2019)
This paper analyzes the responses of teachers in training, who have already taken a course on probability and are students of the Technological Institute of Costa Rica, in a test of probability problem situations in order to assess the handling they make of randomness. The answers show that some do not know how to make explicit the sample space or the random experience, neglect the hypotheses that are needed to use probability as a model and give deterministic answers to random situations. Could it be that probability is taught in a deterministic way?